2016
DOI: 10.1097/brs.0000000000001886
|View full text |Cite
|
Sign up to set email alerts
|

Frailty Index Is a Significant Predictor of Complications and Mortality After Surgery for Adult Spinal Deformity

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
129
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(146 citation statements)
references
References 24 publications
9
129
0
8
Order By: Relevance
“…Because it moves beyond age or any single organ‐system, it has been demonstrated that frailty is a stronger predictor of postoperative outcomes compared with several previous surgical risk‐assessment tools, and it is increasingly recognized as a valuable measure in nononcologic surgical patients . For example, the mFI has been validated in several studies as a reliable measure of postoperative complications, discharge destination, and mortality in vascular, orthopedic, gynecologic, thoracic, and general surgeries . Similarly, it has been demonstrated that phenotypic frailty is predictive of postoperative outcomes in patients presenting for elective surgery, including major abdominal and transplantation surgeries .…”
Section: Frailty and Oncology Surgerymentioning
confidence: 99%
“…Because it moves beyond age or any single organ‐system, it has been demonstrated that frailty is a stronger predictor of postoperative outcomes compared with several previous surgical risk‐assessment tools, and it is increasingly recognized as a valuable measure in nononcologic surgical patients . For example, the mFI has been validated in several studies as a reliable measure of postoperative complications, discharge destination, and mortality in vascular, orthopedic, gynecologic, thoracic, and general surgeries . Similarly, it has been demonstrated that phenotypic frailty is predictive of postoperative outcomes in patients presenting for elective surgery, including major abdominal and transplantation surgeries .…”
Section: Frailty and Oncology Surgerymentioning
confidence: 99%
“…1,2 More recently, the Canadian Study of Health and Aging Frailty Index (CSHA-FI) validated 70 variables as markers of frailty. 3 This has been further refined to form the Modified Frailty Index (mFI), which comprises 11 variables. An individual's mFI is denoted as n/11, wherein n is the number of the 11 variables satisfied.…”
Section: Introductionmentioning
confidence: 99%
“…With such a low proportion, missing data handling techniques are unlikely to affect it [16]. However, there are other aggregate scores of medical condition that can be calculated from NSQIP variables such as the Charlson Comorbidity Index, the Modified Frailty Index, and the Elixhauser Comorbidity Index and have been used in prior database studies [5,24,29]. At least one variable included in each of these is frequently missing in NSQIP.…”
Section: Discussionmentioning
confidence: 99%